Hypothyroidism Is Associated With Coronary Endothelial Dysfunction in Women. Issue 8 (August 2015) - Sara, Jaskanwal D.; Zhang, Ming; Gharib, Hossein; Lerman, Lilach O.; Lerman, Amir
Abstract : Background: Hypothyroidism is associated with an increased risk of coronary artery disease, beyond that which can be explained by its association with conventional cardiovascular risk factors. Coronary endothelial dysfunction precedes atherosclerosis, has been linked to adverse cardiovascular events, and may account for some of the increased risk in patients with hypothyroidism. The aim of this study was to determine whether there is an association between epicardial and microvascular coronary endothelial dysfunction and hypothyroidism. Methods and Results: In 1388 patients (mean age 50.5 [12.3] years, 34% male) presenting with stable chest pain to Mayo Clinic, Rochester, MN for diagnostic coronary angiography, and who were found to have nonobstructive coronary artery disease (<40% stenosis), we invasively assessed coronary artery endothelial‐dependent microvascular and epicardial function by evaluating changes in coronary blood flow (% Δ CBF Ach) and diameter (% Δ CAD Ach), respectively, in response to intracoronary infusions of acetylcholine. Patients were divided into 2 groups: hypothyroidism, defined as a documented history of hypothyroidism or a thyroid‐stimulating hormone (TSH) >10.0 mU/mL, n=188, and euthyroidism, defined as an absence of a history of hypothyroidism in the clinical record and/or 0.3<TSH≤10.0 mU/mL, n=1200. Subjects with a history of hypothyroidism had a significantly lower % Δ CBF Ach (48.26 [80.66] versus 64.58 [128.30]) compared to patients with euthyroidism, while the % Δ CAD Ach did not vary significantly between groups. After adjusting for covariates, females with hypothyroidism still had a significantly lower % Δ CBF Ach (estimated difference in % Δ CBF Ach [SE]: −16.79 [8.18]). Conclusions: Hypothyroidism in women is associated with microvascular endothelial dysfunction, even after adjusting for confounders, and may explain some of the increased risk of cardiovascular disease in these patients.